Methodology for Hydroelectric Potential Evaluation in High Jungle Area with Scarce Topographic and Hydrological Information Using GIS and Algorithm MATLAB - Orozco, Joséc Canales (2022)
Due to scarcity of topographic and hydrological information in high jungle areas, many times projects based on water management are not developed. This is of interest because they involve hydroelectric generation projects. The latter are considered important because of their capacity to satisfy the energy demand of a population and to minimize environmental impact of energy generation. In this sense, we propose a methodology for hydroelectric potential evaluation in high jungle areas that considers the following steps: (a) develop an algorithm in MATLAB in charge of searching geographical conditions for hydroelectric power plant’s location, (b) definition of restrictions: political delimitation, environmental and demographic, (c) generation of average flows based on rainfall-runoff models, estimation of hydroelectric potential and economic evaluation of selected points. The high jungle area studied was Utcubamba basin, in department of Amazonas, Peru, where 2 possible locations with hydroelectric power of 5.33 and 6.09 MW were located.